DEVELOPMENT OF AR-COMIC DIGITAL BOOK BASED ON PANCASILA STUDENT PROFILE TO ENHANCE LEARNING INDEPENDENCE - Tria Aditia Nugraha; Zakiyah Ismuwardani; Mochamad Guntur; Hilda Safitri; Amanda Maharani (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
This study aims to develop an Augmented Reality-Comic Digital Book based on the Pancasila Student Profile to enhance learning independence. The research employs the Research and Development (R&D) methodology, utilizing the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The R&D process involves expert validation and effectiveness testing, using questionnaires and an independent sample t-test with 51 fifth-grade students. The findings indicate that the media is classified within the "very feasible" category, with a material percentage of 93.75% and a media percentage of 91.67%. The novelty of this research lies in the integration of augmented reality technology, digital comics, and the value of the Pancasila Student Profile in one interactive and fun learning product. The findings of this study suggest that the AR-Comic Digital Book has the potential to serve as an innovative media alternative, with the capacity to enhance students' independent character and improve the quality of learning. The AR-Comic Digital Book has been developed to support learning independence and align with the demands of the Merdeka Curriculum, which emphasizes character-based learning and technology.